Challenges of psychiatry in 2011 the Lublin voivodship - Olajossy, Marcin (Current Problems of Psychiatry, 2011)
Author presents Basic data concerning mental health of the population of the Lublin voivodship as well as challenges of the re-forms regarding mental health care in the Lublin voivodship. The necessity of reforms results from the tasks defined by the National Mental Health Programme as well as from problems associated with the contracting of psychiatric services in the Lublin voivodship by National Health Fund (NFZ) for the years 2011-2013. Its implementation enables further, balanced development of inpatient and com-munity mental health care.